2021
DOI: 10.3390/brainsci11081033
|View full text |Cite
|
Sign up to set email alerts
|

Map Learning in Aging Individuals: The Role of Cognitive Functioning and Visuospatial Factors

Abstract: Aging coincides with a decline in map learning ability, but it is unclear to what extent different aspects of the mental representation are susceptible. The present study aimed to investigate knowledge about landmarks, their positions and distances (categorical and distance relations, respectively) in relation to aging as well as cognitive functioning (measured with the Montreal Cognitive Assessment [MoCA]), visuospatial abilities, and self-reported wayfinding inclinations. Thirty young adults and 60 older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…On the other hand, having negative wayfinding inclinations, such as a higher level of spatial anxiety, was found to be related to a lower tendency to go out, fewer experiences of reaching unfamiliar destinations, more experiences of getting lost, and greater map use. These results expand the current knowledge about spatial anxiety implied in decreasing spatial knowledge recall in young [30] and older adults [74], also suggesting its detrimental role in people's spatial behaviors and experiences in daily life. They also call upon the need to consider this aspect as for its applied and clinical value.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, having negative wayfinding inclinations, such as a higher level of spatial anxiety, was found to be related to a lower tendency to go out, fewer experiences of reaching unfamiliar destinations, more experiences of getting lost, and greater map use. These results expand the current knowledge about spatial anxiety implied in decreasing spatial knowledge recall in young [30] and older adults [74], also suggesting its detrimental role in people's spatial behaviors and experiences in daily life. They also call upon the need to consider this aspect as for its applied and clinical value.…”
Section: Discussionsupporting
confidence: 79%
“…In experiments with younger adults, similar to GPS findings, providing maps and verbal directions can improve spatial navigation (Muffato et al, 2021), however, resulting benefits may not be greater than when allowing the person to follow the route for themselves in the environment multiple times (Jaeger et al, 2022).…”
Section: Supporting Spatial Mappingmentioning
confidence: 75%
“…Verbal directions, in contrast, specify a set of instructions, but do not explicitly show the spatial layout. In experiments with younger adults, similar to GPS findings, providing maps and verbal directions can improve spatial navigation (Muffato et al, 2021). However, resulting benefits may not be greater than when allowing the person to follow the route for themselves in the environment multiple times (Jaeger et al, 2023).…”
Section: Supporting Spatial Mappingmentioning
confidence: 78%
“…Providing too much information on maps may overwhelm the memory system of an older adult, however. Muffato et al (2021) for example showed that older adults were not only less accurate in recalling the positions of landmarks on a map, but recalled fewer of them overall. Older adults were also worse at learning locations by viewing them on a map (i.e., allocentrically) compared to navigating through an environment from a first-person perspective (i.e., egocentrically; Yamamoto & DeGirolamo, 2012).…”
Section: Supporting Localizationmentioning
confidence: 99%